LO017: Review of prehospital naloxone use in Ontario: Is a mandatory patch point necessary?. (2nd June 2016) - Charbonneau, V.; Costain, N.; Austin, M.; Willmore, A.; Reed, A.; Maloney, J.; Lewis, J.; Vaillancourt, C.; Dionne, R.
Abstract : Introduction: Recent years have brought an epidemic of opioid abuse to Canada. At present, in Ontario, Naloxone may not be administered by any paramedic without the direct online medical approval of a Base Hospital Physician (BHP). The objective of this study was to review the use of Naloxone by Emergency Medical Service (EMS) personnel, under the existing Advanced Life Support Patient Care Standards (ALS-PCS) medical directive for opioid toxicity, for safety and potential complications that may occur with removal of the mandatory patch point.Methods: This study was a retrospective ambulance call report review of consecutive Naloxone requests placed to a BHP of the Regional Paramedic Program of Eastern Ontario (RPPEO) between Oct 1 st, 2013 and Oct 31 st, 2015. The RPPEO consists of 10 prehospital services, both urban and rural jurisdictions, and has a mix of advance care and primary care paramedics. All ambulance call reports are electronically stored at the secured RPPEO data warehouse. Data was extracted using a standardized data collection tool. All ambulance call reports were reviewed by 2 independent authors (VC, NC). Compliance with the existing medical directive for opioid toxicity was determined. We calculated the frequency of denied Naloxone requests and the rationale for each patch refusal was recorded. We also categorized all adverse events associated with Naloxone administration.Results: From 244 patches, 215 patients were administered Naloxone. Only 7.8% (19/215) of requests for Naloxone were refused; 78.9% (15/19) did not meet existing inclusion criteria for Naloxone administration in the ALS-PCS medical directive for opioid toxicity because the patient's respiration rate was above 12/min. Of the 215 patients who were administered Naloxone, adverse events were extremely uncommon: 5 (2.3%) became violent or verbally abusive, 1 (0.5%) was transiently hypertensive and 4 (1.9%) vomited.Conclusion: Requests for Naloxone to a BHP are common and yet are seldom declined. The use of prehospital Naloxone is associated with few adverse events. These results demonstrate that it would be safe to remove online medical direction for Naloxone from the ALS-PCS medical directive for opioid toxicity if combined with updated paramedic education.